Pengaruh Guru BK dalam Memberikan Motivasi Belajar Kepada Siswa di Sekolah: Array - Ummi Kalsum Hasibuan; Neviyarni (Citra Dharma Cindekia, 2022)
This study aims to fulfill the assignment of the Learning Psychology course taught by Prof. Dr. Neviyarni S., M.S., Kons and to find out the influence of guidance and counseling teachers to encourage students to learn. The research used was using the research library method, which means researching every journal, book and magazine that discusses the influence of the counseling teacher when he has given motivation to learn to his students at school. Counseling teachers play an important role nowadays in shaping students' enthusiasm for learning because there are many influences outside of school that also make students not interested in learning anymore. Therefore, BK teachers provide all means of providing motivation or encouragement to their students in order to create children of the nation who are intelligent and have integrity.